Pembuatan Komposit Hybrid Serat Tandan Kosong Sawit (TKS)/E-Glass Bermatrisks Epoxy Dengan Metode Vacuum Bagging - Febri Dwi Oktriyono; Warman Fatra; Kaspul Anuar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Utilization of Empty Fruit Bunch (EFB) as a fiber in composite materials has a very important meaning as an alternative in overcoming the problem of waste in the palm oil industry. However, natural fibers in composites have poor compatibility with matrix and relatively high absorption of water. Efforts to overcome this problem are with alkaline treatment and adding coupling agents such as Maleated Natural Rubber (MNR). To improve the mechanical properties of composites is to combine synthetic fibers and natural fibers. Synthetic fibers that are often used as composite reinforcing materials are E-Glass fibers. The advantages of E-Glass fiber are that it has high tensile strength, is resistant to chemicals, and has good insulating properties. The purpose of this study was to determine the effect of the percentage ratio of hybrid fiber (E-Glass/TKS/E-Glass), the percentage ratio of hybrid fiber and matrix, the percentage of coupling agent to tensile strength, flexural strength, and water absorption. The experimental design used is the Surface Response-Central Composite Design (RSM-CCD) Method. The results showed that, the tensile strength increased with the addition of the number of E-Glass, whereas for the matrixs and MNR did not significantly affect the tensile strength. Flexural strength increases with the addition of E-Glass and matrix. Water absorption decreases with the addition of MNR. The ultimate tensile strength (75.549 MPa) with the percentage of 40% EFB fiber, 60% matrix and 9% MNR. The flexural strength (149.111 MPa) with the percentage of 40% EFB fiber, 40% matrix and 9% MNR. The lowest water absorption (4.63%) with the percentage of 60% EFB fiber, 40% matrix and 11% MNR.Keywords : Hybrid Composite, EFB, Response surface method, Maleated Natural Rubber (MNR), Vacuum Bagging.